ENHANCING ACCESSIBILITY IN THERAPEUTIC ARCHITECTURE - Okoro, Chinedu P; Nwankwo, Adaeze M (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Therapeutic architecture plays a crucial role in improving the physical, emotional and psychological well being of individuals requiring healthcare services. Therapeutic architecture prioritizes accessibility ensuring all users regardless of their abilities are able to utilize the facility. This paper explores strategies for improving accessibility in therapeutic architecture with the aim of creating inclusive spaces that cater to the diverse needs of its users. Inclusive design is very key in all building types as it fosters a sense of dignity, independence and comfort for users across all demographics. It examines the various physical, sensory and cognitive barriers that limits ease of movement and outlines a framework for solving those challenges.